2018
DOI: 10.3892/mmr.2018.8770
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs RP5-821D11.7, APCDD1L-AS1 and RP11-277P12.9 were associated with the prognosis of lung squamous cell carcinoma

Abstract: Lung squamous cell carcinoma (LUSC), a type of non-small cell lung carcinoma, has a poor therapeutic response, high relapse rate and poor prognosis. The present study was designed to reveal the key long non-coding RNAs (lncRNAs) associated with the prognosis of LUSC. The lncRNA expression profiles of LUSC and adjacent samples were downloaded from The Cancer Genome Atlas database. Based on the edgeR and DEseq packages, the differentially expressed lncRNAs (DELs) between LUSC and adjacent samples were obtained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…APCCD1L-AS1 is reported to significantly distinguish the high-expression group from the low-expression group in lung squamous cell carcinoma. 28 Each of these modules was able to significantly distinguish patients in high-risk groups from those in low-risk groups in terms of overall survival in the luminal subtype ( Figure 5 D). We obtained an RNA-seq dataset of 42 ER-positive (ER + ) breast cancer primary tumors and 30 adjacent breast tissues (GEO: GSE58135 ) to further validate the pattern of lncRNA expression in independent clinical samples.…”
Section: Resultsmentioning
confidence: 96%
“…APCCD1L-AS1 is reported to significantly distinguish the high-expression group from the low-expression group in lung squamous cell carcinoma. 28 Each of these modules was able to significantly distinguish patients in high-risk groups from those in low-risk groups in terms of overall survival in the luminal subtype ( Figure 5 D). We obtained an RNA-seq dataset of 42 ER-positive (ER + ) breast cancer primary tumors and 30 adjacent breast tissues (GEO: GSE58135 ) to further validate the pattern of lncRNA expression in independent clinical samples.…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, increasing evidence indicates that lncRNAs play a potential role as novel biomarkers for prognostic prediction in various cancers. 10 , 11 It was found that a number of lncRNAs were correlated with the prognosis of PTC. Liao et al 12 reported that BANCR could inhibit tumorigenesis in PTC by performing quantitative real-time PCR (qRT-PCR), cell function and tumor xenograft in nude mice, suggesting that BANCR may serve as a novel prognostic marker.…”
Section: Introductionmentioning
confidence: 99%
“…Some lncRNA such as LncRNAs RP5-821D11.7, HULC have been implicated to contribute to the unfavourable prognosis of LUSC (21,22). Recently, LINC00511 has been identified to be the critical factors for carcinogenesis and metastasis in tumors, including glioma, bladder cancer, breast cancer, non-small cell lung cancer (19,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%